2016
DOI: 10.1038/srep27429
|View full text |Cite
|
Sign up to set email alerts
|

NiCo nanoalloy encapsulated in graphene layers for improving hydrogen storage properties of LiAlH4

Abstract: NiCo nanoalloy (4–6 nm) encapsulated in grapheme layers (NiCo@G) has been prepared by thermolysis of a 3D bimetallic complex CoCo[Ni(EDTA)]2·4H2O and successfully employed as a catalyst to improve the dehydrogenation performances of LiAlH4 by solid ball-milling. NiCo@G presents a superior catalytic effect on the dehydrogenation of LiAlH4. For LiAlH4 doped with 1 wt% NiCo@G (LiAlH4-1 wt% NiCo@G), the onset dehydrogenation temperature of LiAlH4 is as low as 43 °C, which is 109 °C lower than that of pristine LiAl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…Many studies have demonstrated that the formed carbon structure during pyrolysis of MOFs precursor acts as dual role, namely, reduction reagent to reduce metal ions into active metal phase and conductive support for dispersed metal nanoparticles. 19,22,29 In this study, relatively uniformly dispersed nanoparticles with sizes of 5.0~15 nm can be clearly observed on carbon sheets after pyrolysis treatment of Co/Ni MOFs precursor, exhibiting an average particle size of ~7.9 nm (Fig. 2d).…”
Section: Resultssupporting
confidence: 53%
See 3 more Smart Citations
“…Many studies have demonstrated that the formed carbon structure during pyrolysis of MOFs precursor acts as dual role, namely, reduction reagent to reduce metal ions into active metal phase and conductive support for dispersed metal nanoparticles. 19,22,29 In this study, relatively uniformly dispersed nanoparticles with sizes of 5.0~15 nm can be clearly observed on carbon sheets after pyrolysis treatment of Co/Ni MOFs precursor, exhibiting an average particle size of ~7.9 nm (Fig. 2d).…”
Section: Resultssupporting
confidence: 53%
“…Also, we found that the distribution of S element is more obvious located at CoNi nanoparticles, possibly meaning the formation of sectional Co or/and Ni sulfides during pyrolysis of Co/Ni MOFs. This could 22 The actually measured atomic ratio of Co to Ni is 0.89 (slightly lower than 1:1) in CoNi@SNC sample by ICP-OES, possibly meaning partial Ni 2+ substituting Co 2+ in MOFs structure. Except for the diffraction peaks of CoNi alloy, several weaker diffraction peaks at 2θ=29.8, 41.5, 47.4° can be ascribed to the (311) plane of cubic Co9S8 and (010), (011) planes of hexagonal Co, indicating a coexistence of Co9S8, hexagonal Co and CoNi alloy after pyrolysis of Co/Ni MOFs nanosheets.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…[33] Deconvolution of the N 1s XPS spectrum (Figure 4b) revealed two different kinds of nitrogen atoms: 64 % of pyridinic N (398.6 eV) and 34.8 % of graphitic N (400.8 eV) atoms. Binding energies of 852.7 and 869.6 eV revealed the presence of metallic nickel (Ni 0 ) in the NiCo@GC-600 catalyst; [35] in addition, the two major-intensity peaks having binding energies of 855.1 and 872.5 eV confirmed the presence of oxidized metallic nickel species, arising from surface oxidation; [36] furthermore, strong satellite peaks at 861.3 and 879.6 eV revealed that the majority of the surface nickel was in the higher oxidation state of Ni 2 + . Binding energies of 852.7 and 869.6 eV revealed the presence of metallic nickel (Ni 0 ) in the NiCo@GC-600 catalyst; [35] in addition, the two major-intensity peaks having binding energies of 855.1 and 872.5 eV confirmed the presence of oxidized metallic nickel species, arising from surface oxidation; [36] furthermore, strong satellite peaks at 861.3 and 879.6 eV revealed that the majority of the surface nickel was in the higher oxidation state of Ni 2 + .…”
Section: Resultsmentioning
confidence: 99%